Electrocardiographic Intervals Associated with Incident Atrial Fibrillation: Dissecting the QT-interval - Roberts, Jason D. (Heart Rhythm, 2017)
BACKGROUND: Prolongation of the QT-interval has been associated with an increased risk for developing atrial fibrillation (AF), but the responsible mechanism remains unknown. OBJECTIVE: To sub-divide the QT-interval into its components and identify the resultant lectrocardiographic interval(s) responsible for the association with AF. METHODS: Pre-defined QT-interval components were assessed for association with incident AF in the Atherosclerosis Risk in Communities (ARIC) Study using Cox proportional hazards models. Hazard ratios were calculated per 1-standard deviation increase in each component. Among QT-interval components exhibiting significant associations, additional analyses evaluating long extremes, defined as greater than the 95(th) percentile, were performed. RESULTS: Among 14,625 individuals, 1,505 (10.3%) were diagnosed with incident AF during a mean follow-up period of 17.6 years. Following multivariable adjustment, QT-interval components involved in repolarization, but not depolarization, exhibited significant associations with incident AF, including a longer ST-segment (Hazard Ratio [HR]: 1.27; 95% Confidence Interval [CI]: 1.14–1.41], p<0.001) and a prolonged T-wave onset to T-wave peak (T-onset to T-peak) (HR: 1.13; 95% CI: 1.07–1.20, p<0.001). Marked prolongation of the ST-segment (HR: 1.31; 95% CI: 1.04–1.64, p=0.022) and T-onset to T-peak (HR: 1.36, 95% CI: 1.09–1.69, p=0.006) was also associated with an increased risk of incident AF. CONCLUSIONS: The association between a prolonged QT-interval and incident AF is primarily explained by components involved in ventricular repolarization; prolongation of the ST-segment and T-onset to T-peak. These observations suggest that prolongation of Phases 2 and 3 of the cardiac action potential drives the association between the QT-interval and AF risk.